Wallander's Dark Geopolitics - Stougaard-Nielsen Jakob (Nordicom Review)
A current fault line in the study of crime fiction as a transnational genre is to what extent crime novels offer readers genuine cosmopolitan windows onto other worlds and cultures or whether it simply is bound to reproduce trite imagologies and national stereotypes. The overarching premise for this article is to explore the extent to which Henning Mankell's crime novels and their adaptations engage the character Wallander's own and “other” worlds with a cosmopolitan perspective, by considering the mutations of Wallander's fictional local world as intricately tied to discursive geopolitical realities of the post–Cold War world. More specifically, I consider what may be gained from exploring the Wallander series within two distinct – yet, I shall argue, related – perspectives on geopolitics and crime fiction: on the one hand, the geopolitics of the translation, adaptation, and reception networks that have “worlded” the Wallander series (what I call Wallander's geopolitical adaptation networks), and on the other, the fictional geopolitical networks that weave the Global North and the Global South together in several of Mankell's intricate crime plots (Wallander's dark geopolitics).